An automatic monitoring and control system inside greenhouse - Hassan, Niamul; Abdullah, Shihab Ibne; Noor, Ahmad Shams; Alam, Marzia Ruman (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 3rd International Conference on Green Energy and Technology, ICGET 2015; University of DhakaDhaka; Bangladesh; 11 September 2015 through 12 September 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICGET.2015.7315084